What matters in policing? : change, values and leadership in turbulent times - Dijk, Auke van; Hoogewoning, F. C. (Frank C.); Punch, Maurice (Policy Press, 2015)
Policing is at a turbulent turning point: the pace of change is accelerating with renewed emphasis on crime reduction yet with austerity. This topical book examines what matters in policing, rather than just what works. It compares the implications of restructuring in the UK and The Netherlands, also in the USA, regarding police systems, policing paradigms and research knowledge. The authors, who cover both academia and practice, focus particularly on dilemmas for police leadership relating to strategy, values and operational command. With a foreword by Peter Neyround, University of Cambridge, it argues for developing confident and competent leadership and also provide a comprehensive paradigm to chart policing in the future while retaining trust. It is accessibly written for academics, practitioners, policy makers and students in diverse societies.